The Role of Environmental Risk Perception as a Mediator in the Relationship Between Eco-Anxiety and Pro-Environmental Behavior Among Generation Z in Lampung - Sri Ilham Nasution; Rahmad Purnama; Violla Dwi Puspita (Universitas Katolik Soegijapranata, 2025)
Exposure to environmental issue–related information may enhance moral awareness, encouraging individuals to act in environmentally responsible ways. However, psychological factors such as eco-anxiety are often required to strengthen the intention to engage in pro-environmental behavior. This study examines whether eco-anxiety contributes to pro-environmental behavior among Generation Z in Lampung through the mediating role of environmental risk perception. Using a purposive sampling technique, data were collected from 305 Generation Z respondents (aged 13–28 years). This study employed a quantitative approach and used SEM-PLS for data analysis, with model fit criteria assessed using SRMR and NFI. The results show that: (1) eco-anxiety has a significant effect on environmental risk perception (p = 0,000; t = 12.718), (2) eco-anxiety has a significant effect on pro-environmental behavior (p = 0,000; t = 5.434), (3) environmental risk perception has a significant effect on pro-environmental behavior (p = 0,000; t = 5.994), and (4) environmental risk perception significantly mediates the relationship between eco-anxiety and pro-environmental behavior (p = 0,000; t = 5.117).